Pengembangan Konsep Indo-Pasifik: Sebuah Konstruksi Geopolitik Indonesia di Kawasan Melalui ASEAN - Pradipta Nindyan Saputra; Arfin Sudirman (Sospol : Jurnal Sosial Politik, 2020)
Abstract The concept of geopolitics appears to bridge the relationship between geographical factors in contemporary politics. Through its focus on geographical factors, geopolitics has a very materialistic and objective foundation. Based on a critical examination of the implementation of the concept, it becomes clear that the geopolitical framework depends on social construction. Through qualitative methods, this article tries to explain that the concept of "Indo-Pacific" which is of international concern at the moment, is inseparable from a geopolitical construction carried out by the countries concerned. The significance of this new regional concept has been contested by some countries such as the United States, China, India, Australia, and Japan. Seeing its position at the Indo-Pacific geopolitical junction, Indonesia felt the need to make a geopolitical construction effort to encourage the creation of a better regional ecosystem, not as an arena for conflicting interests, as happened in the Asia-Pacific region. As part of the geopolitical construction effort and changing perceptions of all countries in the region, Indonesia through the ASEAN framework continues to promote the Indo-Pacific region which is open, free, and inclusive in various international forums.